Initial investigation on hetero-dinuclear ball-type metallo phthalocyanines as a photosensitizing dye - Sahin, Safinaz; Kaya, Esra Nur; Durmuş, Mahmut; Odabas, Zafer (Elsevier, 2025)
The synthesis of novel peripherally short-bridged (3,5-di-tert-butylbenzene-1,2-bis(olate)) and long-bridged (2,2 '((3,5-di-tert-butyl-1,2-phenylene)bis-(oxy))bis(ethan-1-olate)) homodinuclear and heterodinuclear metallo balltype phthalocyanines (Zn2Pc2 ' s (3 and 4), Lu2(OAc)2Pc2 ' s (5 and 6) and (ZnLu(OAc)Pc2 ' s (7 and 8)) were described, and the molecular structures of new starting material compounds (1 and 2), and that of novel metallophthalocyanines (3-8) were characterized by standard spectroscopic methods. In this study, the connecting bridge lengths were changed for the first time in homodinuclear and heterodinuclear metallo ball-type Pcs, and how this modification changed the spectral and photophysicochemical properties was investigated. In addition, the nature of metal in the phthalocyanine cavity on the photophysical and photochemical properties was investigated by comparing with unsubstituted phthalocyanine derivatives.
Keywords: Dinuclear; Ball-type phthalocyanine; Photosensitizing dye; Photophysical; Photochemical